PENYULUHAN PENDIDIKAN DAN PEREMAJAAN SARANA PENDIDIKANDI PULAU BUKU LIMAU, KABUPATEN BELITUNG TIMUR - Juwita, Silvia Ratna (Universitas Esa Unggul, 2019)
AbstractBuku Limau Island is located in Bangka Belitung Province, there have only kindergarten and elementary school level which available in the island. Those facilities support educational activities so that many of them have no formal education and educational support facilities in the form of a library which provided sources of information as a medium for student learning is also not sufficient because there are less organized and the number of sources of books available, which triggers a lack of interest in reading students. The method was used an individual approach carried out in groups into three parts (edu-support team, motivation team, and counseling team). The activities was found several results from three aspects: (1) Motivation Team, found the level of interest of students towards different learning; (2) The Counseling Team was formed a youth organization to organize the Buku Limau Island community activities, such as competitions, routine recitation, mutual cooperation, etc.; (3) Edu-Support Team, improvement of 3 educational facilities, there were school library, village reading park, and public space.Ã‚Â Keywords:buku limau, belitung, abdimasÃ‚Â AbstrakPulau Buku Limau merupakan salah satu gugusan pulau di Desa Buku Limau, Kecamatan Manggar, Kabupaten Belitung Timur, hanya terdapat PAUD dan SD yang terdapat di Pulau Buku Limau yang menunjang kegiatan pendidikan sehingga banyak dari mereka kurang mengenyam pendidikan secara formal dan fasilitas penunjang pendidikan berupa perpustakaan yang memberikan sumber informasi sebagai media pembelajaran siswa juga tidak cukup memadai karena kurang tertata dan jumlah sumber buku yang tersedia sehingga memicu kurangnya minat baca siswa.Metode yang digunakan adalah pendekatan secara individual yang dilaksanakan berkelompok menjadi tiga bagian (tim edu-support, tim motivasi, dan tim bimbingan konseling). Ditemukan beberapa hasil dari tiga aspek: (1) Tim Motivasi, ditemukan tingkat minat siswa terhadap pembelajaran yang berbeda-beda; (2) Tim Konseling, membentuk organisasi remaja karang taruna guna menggerakkan kegiatan bermasyarakat Pulau Buku Limau, seperti lomba-lomba, pengajian rutin, gotong royong, dan lain sebagainya; (3) Tim Edu-Support, perbaikan 3 sarana pendidikan yaitu perpustakaan sekolah, taman baca desa, dan lapangan serbaguna.Ã‚Â Kata kunci: buku limau, belitung, abdimas,